Costos económicos de producción de la caña de azúcar saccharum officinarum en el cantón Catamayo provincia de Loja - Torres Vallejo, Kelly (2005)
It was carried out an investigation on the costs of the existent systems of production of sugarcane in the canton Catamayo, province of Loja. The objectives of this investigation were the following: To establish the costs of Investment and Production in a hectare of sugarcane, so much of the system technified, semitechnified as of non technified in the canton Catamayo, province of Loja, and; to analyze the economic difference of the three systems of production of sugarcane (system technified, semitechnified and non technified). Personal surveys to 60 sugarcane growers were carried out in the canton Catamayo. The re-sults establish that the investment costs and production differ substan-tially in the three systems. It was concluded: The investment costs in a hectare of sugarcane are higher in the technified system, then is the non technified and is lower in the semitechnified system. The produc-tion costs in a hectare of sugarcane are higher in the system tecnifica-do, then is the system semitecnified and it is lower in the system non tecnified. The revenues for sale of the production are higher in the system technified and almost the same in the systems semitechnified and non technified. The best economic alternative of production of sugarcane is in the technified farms for theirs highest production.